Introduction to Unified Strength Theory - Yu, Maohong, 1934-; Yu, Shu-Qi. (Milton : CRC Press LLC, 2019)
Strength theory deals with the yield or failure of materials under complex stress state. It is very important in mechanics of materials, strength of structures, and mechanical and civil engineering. Unified strength theory is a series of yield criteria and failure criteria other than a single strength theory. The unified strength theory can be adopted for various kinds of materials, such as metallic materials, geomaterials, polymers etc. It is the solution to the Voigt-Timoshenko Conundrum. Its limit surfaces cover all regions of the convex strength theory from the lower bound to the upper bound. This book gives a clear and brief description about the unified strength theory both in figures and text. Some applications of unified strength theory are also given in this book. This book is suitable for undergraduate students, who are studying the mechanics of materials and engineering mechanics, as well as for graduate students who are interested in this field. Researchers and engineers can also benefit from this book.
5.12 Unified solution of plastic limit internal pressure for a thick-walled cylinder with different tensile strength and compressive strength materials5.13 Barrel strength design of artillery; 5.14 The economic significance of the use of Yu-unified strength theory; 5.15 Procedure of the applications of the Yu-UST and Yu-UYC; 5.16 Summary; References; Readings
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Strength of materials -- Mathematical models; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; TECHNOLOGY / General; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical